Entropic lattice Boltzmann simulation of three-dimensional binary gas mixture flow in packed beds using graphics processors. (2016) - Safi, Mohammad Amin; Ashrafizaadeh, Mahmud
The lattice Boltzmann method is employed for simulating the binary flow of oxygen/nitrogen mixture passing through a highly dense bed of spherical particles. Simulations are performed based on the latest proposed entropic lattice Boltzmann model for multi-component flows, using the D3Q27 lattice stencil. The curved solid boundary of the particles is accurately treated via a linear interpolation. To lower the total computational cost and time of the simulations, implementation on graphics processing units (GPU) is also presented. Since the workload associated with each iteration is relatively higher than that of conventional 3D LBM simulations, special emphasis is paid in order to obtain the best computational performance on GPUs. Performance gains of one order of magnitude over optimised multi-core CPUs are achieved for the complex flow of interest on Fermi generation GPUs. Moreover, the numerical results for a three-dimensional benchmark flow show excellent agreements with the available analytical data.